2011
DOI: 10.1007/s10549-011-1455-9
|View full text |Cite
|
Sign up to set email alerts
|

A single-center, prospective and randomized controlled study: Can the prophylactic use of lamivudine prevent hepatitis B virus reactivation in hepatitis B s-antigen seropositive breast cancer patients during chemotherapy?

Abstract: Over the past four decades, chemotherapy has played an important role in prolonging survival in breast cancer patients. However, it may also result in undesirable side effects such as hepatitis B virus (HBV) reactivation seen in this study. With the increasing use of chemotherapy paralleling the rise in breast cancer incidence, the occurrence of HBV reactivation is likely to further increase. Several strategies use lamivudine to deal with this problem. Initially, lamivudine had been used to treat patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 42 publications
1
50
0
1
Order By: Relevance
“…Many studies have shown the effect of lamivudine as a prophylactic antiviral therapy on HBV reactivation (Table 2) [75][76][77]. In a meta-analysis, prophylactic lamivudine therapy prior to chemotherapy in cancer patients decreased the risk of HBV reactivation (4% vs. 37%), HBV-related hepatitis (4% vs. 33%), liver failure (0% vs. 13%), and mortality (2% vs. 7%) compared to placebo [5].…”
Section: Prophylaxis Of Hbv Reactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown the effect of lamivudine as a prophylactic antiviral therapy on HBV reactivation (Table 2) [75][76][77]. In a meta-analysis, prophylactic lamivudine therapy prior to chemotherapy in cancer patients decreased the risk of HBV reactivation (4% vs. 37%), HBV-related hepatitis (4% vs. 33%), liver failure (0% vs. 13%), and mortality (2% vs. 7%) compared to placebo [5].…”
Section: Prophylaxis Of Hbv Reactivationmentioning
confidence: 99%
“…However, patients with long-term therapy with tenofovir should beware of kidney toxicity [82,83]. If the cost is a major hindrance to anti-viral prophylaxis, lamivudine may be considered in patients with serum HBV DNA levels <2,000 IU/mL because HBV reactivation had not occurred in patients with serum HBV DNA levels <2,000 IU/mL regardless of antiviral agents [76]. Even though the duration of prophylactic antiviral treatment is controversial, the treatment should be maintained for at least 6 to 12 months after withdrawal of immunosuppressive agents.…”
Section: Prophylaxis Of Hbv Reactivationmentioning
confidence: 99%
“…Most recently, a systematic review and metanalysis of 5 randomised controlled trials comparing antiviral prophylaxis to treatment at the onset of HBVr has been published [63] . Lamivudine was used in 4 studies and entecavir was used in 1 study [8,[92][93][94][95] . The overall risk ratio (RR) favoured the prophylactic use of antivirals over no antivirals [RR = 0.13 (0.06-0.30)] [63] .…”
Section: Prevention Of Hbvrmentioning
confidence: 99%
“…Recently, the American Gastroenterological Association guidelines recommend screening for HBV (HBsAg and antiHBc, followed by a sensitive HBV-DNA test in case of positivity for either one or the other test, or both tests) in patients at moderate or high risk who will undergo ISDT, so the HBV screening may be cost-effective in patients with breast cancer slated to receive adjuvant chemotherapy if HBV infection is prevalent [4] . About 20% of untreated HBsAg-positive patients with breast cancer undergoing chemoteraphy develop HBVr, in these studies anthracycline-based therapy was used by all investigators [5][6][7] and glucocorticoids were routinely administered in 2 studies. Despite in literature capecitabine does not result in acute hepatitis B reactivation [8] ; we report a case of HBVr leading to exitus in a female patient with breast cancer treated using capecitabine.…”
Section: Introductionmentioning
confidence: 99%